The Risk Level of Viet Nam Wholesale and Retail Good Industry Under Financial Leverage During and After The Global Crisis 2009-2011 - Ngoc Huy, Dinh Tran (International Journal For Research In Business, Management And Accounting, 2015)
This paperwork evaluates the impacts of external financing on market risk for the listed firmsin the Viet nam wholesale and retail industry, esp. during and after the financial crisis 2009-2011.First of all, by using quantitative and analytical methods to estimate asset and equity beta oftotal 9 listed companies in Viet Nam wholesale and retail industry with a proper traditionalmodel, we found out that the beta values, in general, for many institutions are acceptable.Second, under 3 different scenarios of changing leverage (in 2011 financial reports, 30% upand 20% down), we recognized that the risk level, measured by equity and asset beta mean,decreases when leverage increases to 30% but increases more if leverage decreases down to20%.Third, by changing leverage in 3 scenarios, we recognized the dispersion of risk level,measured by equity beta var, increases from 0,062 to 0,088 if the leverage increases to 30%whereas decreases to 0,052 if leverage decreases to 20%. But the dispersion measured byasset beta var decreases to 0,022 (leverage down 20%), showing leverage efficiency.Finally, this paper provides some outcomes that could provide companies and governmentmore evidence in establishing their policies in governance.